Peningkatan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Problem Based Learning (PBL) Pada Kelas X.1 UPT SMA Negeri 3 Maros - Nur Rezky Mauliana J; Nurul Maghfirah; Roslindasari Roslindasari (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
Mathematics as a form of learning that has great meaning in life has a direct role that is efficient, effective, careful and rational. Student learning outcomes can be supported through the learning process carried out. The purpose of this writing is to analyze improving student mathematics learning outcomes through the Problem Based Learning (PBL) learning model in class X.1 UPT SMA Negeri 3 Maros. The research design used was PTK (Classroom Action Research). The results obtained in the percentage obtained in cycle I was 60.00% with an average value of 79.00. Based on this, it can be qualified as "Low". Meanwhile in cycle II the percentage obtained in cycle I was 100% with an average value of 99.20. Based on this, it can be qualified as "High". The conclusion explains that mathematics learning outcomes can be improved by using the PBL model. The material used as implementation material is Arithmetic and Geometry Detets. Individual learning outcomes can be interpreted as results resulting from students based on the learning process. Changes that occur within a person can be implemented through meaningful learning outcomes which include skills, skills, behavior, attitudes, understanding and knowledge.